Completing the Basic and Clinical Science Course as a First-Year Ophthalmology Resident - Oke, Isdin; Siegel, Nicole H.; Peeler, Crandall E.; Ness, Steven D.; Ramsey, Jean E. (Journal of Academic Ophthalmology, 2019)
Background The Basic and Clinical Science Course (BCSC) is the primary educational curriculum for ophthalmology resident physicians in the United States. The Ophthalmic Knowledge Assessment Program (OKAP) examination is an annual evaluation completed by residents that is based primarily on the BCSC curriculum. First-year ophthalmology residents are encouraged to complete the 13 volume BCSC series in preparation for the OKAP examination while balancing a steep clinical learning curve and substantial call schedule. By calculating the daily time commitment necessary to read each volume in the series, we hope to help residents create a realistic study plan to compete the entire BSCS series before the OKAP examination.Methods We determine the word counts of each volume using an electronic copy of the 2018–2019 BCSC series. We include all text sections and legends, and we exclude all figures and tables. We calculate the time per day of dedicated reading required to complete a goal number of BCSC books between the start of ophthalmology residency (postgraduate year 2 [PGY2]) and the OKAP examination by developing a formula that is a function of self-assessed reading speed.Results A first-year ophthalmology (PGY2) resident with an average reading speed of 250 words per minute must read for 25.0 minutes per day to complete the entire BCSC series before the OKAP examination. If studying is initiated at the beginning of intern (PGY1) year, the resident must read for 10.2 minutes per day. We introduce a formula and provide a table to guide residents on the amount of time needed to dedicate to reading the BCSC each day as a function of self-assessed reading speed.Discussion Completion of all volumes of the BCSC requires a daily commitment with little room for missed sessions. The commitment is substantially more realistic if initiated during the PGY1 year; thus, residency programs should encourage an early start to OKAP preparation. We hope with a better understanding of the daily time commitment involved in completing the BCSC series, ophthalmology residents will be able to develop more successful study plans.
Keywords: Basic Clinical Science Course; Ophthalmology Knowledge Assessment Program; reading speed; study schedule